Confronting the invasive species crisis with metamodel analysis: An explicit, two-species demographic assessment of an endangered bird and its brood parasite in Puerto Rico. (April 2016) - Miller, Philip S.; Lacy, Robert C.; Medina-Miranda, Roseanne; López-Ortiz, Ricardo; Díaz-Soltero, Hilda
Abstract: Invasive species pose a significant threat to native species persistence worldwide. Effective invasives management requires a detailed understanding of the mechanisms by which they impact native taxa, yet most quantitative models used to inform management do not address these complex interactions. Populations of the endangered Yellow-shouldered Blackbird ( Agelaius xanthomus, YSBL) have declined dramatically across southwestern Puerto Rico, largely through brood parasitism by the invasive Shiny Cowbird ( Molothrus bonariensis, SHCO). YSBL management is focused on removing SHCO eggs from Blackbird nests and on constructing artificial nest structures (ANS) that are resistant to terrestrial predators and easily monitored for SHCO parasitism. Despite these efforts, successful recovery of YSBL requires a more thorough knowledge of the complex two-species system. We used a new "metamodel" approach to explicitly simulate demographic interactions between these two species. The metamodel featured two separate, individual-based demographic models running concurrently, with specific data-driven linkages simulating the species interactions and their impacts on population dynamics. Results indicated that YSBL management may be most effective by direct removal of SHCO eggs from parasitized nests, which can also reduce the number of fledged Cowbirds that subsequently prefer YSBL nests as adults. Fledging success and post-fledging survival, previously not considered serious threats, were also identified as critical determinants of YSBL population viability and important targets for management. Importantly, trapping of SHCO did not emerge as an effective method of YSBL management. This is among the first population viability simulation models featuring explicit, simultaneous treatment of linked demographic dynamics in a native-invasive species system. Highlights: Used a new approach to simulate linked demographic dynamics between two bird species Complex interactions between native Blackbird and invasive Cowbird in Puerto Rico Successful Blackbird nest management requires continued removal of Cowbird eggs. Cowbird trapping alone cannot result in long-term Blackbird population viability. Modeling approach in an important tool that can assist invasive species management